(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Concrete is used for construction most of the buildings and bridges in India can be called as back-bone to the infrastructural development of the nation. But the increase in cost of the cement not only increases the budget of a building but also poses a serious threat to the country’s development. It is identified that some industrial waste products like Bagasse Ash are having some cementitious and siliceous properties. So the use of the industrial and agricultural wastages in concrete partly as cement replacement, reduce the cost of making concrete, also causes improvement in the properties of concrete and reduce environmental pollution. Sugarcane bagasse is a byproduct of the sugarcane industry that is used as fuel. The combustion process produces ashes that are mostly composed of unburned materials, silicon and aluminum oxides. Prior research has reported satisfactory improvement, partly due to the filler effect and the Pozzolanic reaction between reactive Silicone Dioxide (Sio 2) from the "SCBA" and Calcium Hydroxide (Ca(oH) 2) from cement hydration, when this ash is added as a substitute for cement while mixing concrete. The concrete cubes are cast with bagasse ash as a cement substitute (i.e. 10%, 20%,30%) and various combinations of SCBA and M-Sand (10%, 20%, and 30%) with M25,M30 andM35 grades. The mechanical properties of concrete such as compressive strength and split tensile strength using the mix made by sugar bagasse ash and M-Sand is analyzed and compare it with the conventional concrete.